Remnant cholesterol and its variability independent of low density lipoprotein cholesterol predict metabolic dysfunction associated steatotic liver disease - Yuting Sun; Xinlei Miao; Manling Hu; Xiaoling Xie; Shuang Liu; Ziping Song; Jiayi Deng; Fei Xu; Meng Li; Yangxuan He; Song Leng (Scientific Reports)
Abstract This study aimed to determine whether remnant cholesterol (RC) and its variability can predict the onset of metabolic dysfunction-associated steatotic liver disease (MASLD) independently of low-density lipoprotein cholesterol (LDL-C) levels. A longitudinal cohort study involving 43,065 participants who underwent at least two physical examinations was conducted. This study used Cox proportional hazards models to assess the relationships among RC quartile levels (Q1–Q4), visit-to-visit variability, and the risk of MASLD. This variability was quantified using several metrics: standard deviation (SD), logSD, average real variability (ARV), logARV, mean absolute deviation (MAD), and logMAD. Concurrently, this study utilized a combined analysis of RC and LDL-C groups to assess the independent risk of MASLD associated with RC. During a mean visit-to-visit of 3.19 years (SD 2.06 years), 8374 patients (19.45%) developed MASLD. Compared with Q1, Q4 was associated with a significantly greater risk of MASLD (hazard ratio [HR] 1.309, 95% confidence interval [CI] 1.220–1.403, P < 0.001). The fully adjusted Cox model revealed that the HRs of SD, logSD, ARV, logARV, MAD and logMAD were 1.400 (95% CI 1.305–1.502), 1.278 (95% CI 1.188–1.374), 1.152 (95% CI 1.079–1.229), 1.183 (95% CI 1.140–1.227), 1.578 (95% CI 1.433–1.737) and 1.263 (95% CI 1.175–1.358), respectively. In both LDL-C subgroups (≥ 3.4 mmol/L and < 3.4 mmol/L), high baseline RC was associated with elevated MASLD risk (HR 1.208, 95% CI 1.148–1.270, P < 0.001; HR 1.246, 95% CI 1.129–1.374, P < 0.001). RC levels were independently associated with MASLD in healthy individuals, irrespective of LDL-C level. The variability of RC during visit-to-visit periods provides a predictive marker for identifying individuals at heightened risk of MASLD.